The Risk Sharing in The Contracts in The Systems of Urban and Regional Transport - Gross Costs Contracts Vs Net Costs Contracts - Grzegorz DYDKOWSKI; Anna URBANEK; Wiktoria GALECKA (Communications of International Proceedings, 2024)
Since the arrangements in the field of duties and risks sharing may be one of the factors of the increased quality and economy of urban public transport services, the study is aimed at the identification, assessment, and allocation of selected risk types between the parties to gross and a net costs contracts in the urban and regional transport. This research was based on the: subject’s literature, the analysis of collected figures, of the available results of studies, the methods of analogy, brainstorming and synthesis as well as on the own practical experience in the management of a big public transport system in the central part of the Silesian Voivodeship in Poland. Hence the drawbacks and advantages of the mentioned contract models have been shown as well the conditions, which are in favour of their application. The results show among others the importance of appropriate designing of the contracts and their impact on the participation and involvement of the transport carriers in the actions intended to improve the quality of transport and hence the number of transported passengers. The net costs contracts motivate the carriers to active actions related to the volume of transport and revenues on that; in turn, the gross costs contracts are a better solution under the conditions of many carriers’ existence and the strategy of public transport integration. The gross costs contracts should be supplemented with motivation provisions for the entities providing the transport services, to increase their quality and effectiveness.
Keywords: risk; gross costs contracts; net costs contracts; urban public transport